Occupational and environmental exposures associated with testicular germ cell tumours: systematic review of prenatal and life-long exposures. - Rémi Béranger; Charlotte Le Cornet; Joachim Schüz; Béatrice Fervers (PLoS ONE)
Background Testicular germ cell tumours (TGCT) are the most common cancers in men aged between 15 and 44 years and the incidence has increased steeply over the past 30 years. The rapid increase in the incidence, the spatial variation and the evolution of incidence in migrants suggest that environmental risk factors play a role in TGCT aetiology. The purpose of our review is to summarise the current state of knowledge on occupational and environmental factors thought to be associated with TGCT. Methods A systematic literature search of PubMed. All selected articles were quality appraised by two independent researchers using the 'Newcastle-Ottawa Quality Assessment Scale'. Results After exclusion of duplicate reports, 72 relevant articles were selected; 65 assessed exposure in adulthood, 7 assessed parental exposures and 2 assessed both. Associations with occupation was reported for agricultural workers, construction workers, firemen, policemen, military personnel, as well as workers in paper, plastic or metal industries. Electromagnetic fields, PCBs and pesticides were also suggested. However, results were inconsistent and studies showing positive associations tended to had lower quality ranking using the assessment scale (p=0.02). Discussion Current evidence does not allow concluding on existence of any clear association between TGCT and adulthood occupational or environmental exposure. The limitations of the studies may partly explain the inconsistencies observed. The lack of association with adulthood exposure is in line with current hypotheses supporting the prenatal origin of TGCT. Future research should focus on prenatal or early life exposure, as well as combined effect of prenatal and later life exposure. National and international collaborative studies should allow for more adequately powered epidemiological studies. More sophisticated methods for assessing exposure as well as evaluating gene-environment interactions will be necessary to establish clear conclusion.